KONFIGURASI SUMBER DAYA DAN STRATEGI BERKOMPETISI - STUDI KASUS PERUSAHAAN KECIL DAN MENENGAH INDONESIA - HERU SATYANUGRAHA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
This study explores the relation between the resources of Indonesian small and medium firms, and their competitive strategy in the export market. Resource-based theory is used to model the relationship. The findings indicate that the relationship exists. Cluster analysis reveals that Indonesian small and medium firms can be classified into four different groups based on their resources configuration: business, bureaucratic, improverishedm and technological firms. There is relationship between the grouping of the firms and their competitive strategies.